Health status and public health in Asia (Italian Journal of Public Health, 2011)
After the thematic issues devoted to Public Health in Eastern Europe [1] and in the Americas [2], in the current issue the Italian Journal of Public Health six articles will face different aspects regarding themes of health status and public health in Asia, giving a description of infection, nutritional and health care organization problems, and linking them to social, demographic and religious features. In each article indeed strictly health topics can be understood considering the peculiar and heterogeneous characteristics of the developing countries.